Gastroprotective Potential of Medicinal Plant From Central Kalimantan: Sungkai Leaves (Peronema canescens Jack)-Ultrasonic Assisted Extraction in Rats Induced with Absolute Ethanol - Savitri, Dilasari; Trinovita, Elsa; Widayati, Ratna; Handayani, Septi; Nugrahini, Sintha (UI Scholars Hub, 2025)
Peptic ulcer disease is a gastrointestinal disorder associated with significant morbidity and mortality. Enhancing the quality of life of patients with peptic ulcers often involves integrating conventional treatments with complementary alternative therapies. One such alternative therapy is herbal remedies, which local communities have long recognized. Sungkai leaves (Peronema canescens Jack) contain various bioactive components, including flavonoids, alkaloids, saponins, tannins, steroids, and phenolic compounds. This study aimed to assess the gastroprotective properties of sungkai leaf extract (Peronema canescens Jack) by analyzing the average size of gastric lesions in male Wistar rats exposed to absolute ethanol. The research used a true experimental design with a posttest-only control group approach involving six treatment groups, each consisting of four rats. Gastroprotective activity was macroscopically evaluated by measuring the average size of the gastric lesions. Statistical analyses were conducted using the Kruskal-Wallis and Mann-Whitney tests for post hoc comparisons. Results showed that the normal group had an average lesion size of 0 mm, the negative control group had 115.37±50.53 mm, and the positive control group had 7.40±2.57 mm. For the groups treated with sungkai leaf extract, the 100 mg/kgBW dose resulted in 6.86±3.83 mm lesions, the 200 mg/kgBW dose in 9.65±10.27 mm, and the 400 mg/kgBW dose in 29.50±19.68 mm. Statistical analysis using SPSS 26 revealed a significant difference between the groups,with a Kruskal-Wallis test result of p=0.002. These findings show that sungkai leaf extract exhibits gastroprotective activity compared with omeprazole, as seen by the smaller average size of gastric lesions in male Wistar rats treated with absolute ethanol.